Development of Criteria for the Use of Asphalt-Rubber as a Stress-Absorbing Membrane Interlayer (SAMI). - Newcomb,D E; McKeen,R G (1983)
This report documents over 2 years of research efforts to characterize asphalt-rubber mixtures to be used in Stress-Absorbing Membrane Interlayers (SAMI). The purpose of these SAMIs is to retard or prevent reflection cracking in asphalt-concrete overlays. Several laboratory experiments and one field trial were conducted to define significant test methods and parameters for incorporation into construction design and specification documents. Test methods used in this study included a modified softening point test, force-ductility, and Schweyer viscosity. Variables investigated included (1) Laboratory-mixing temperature; (2) Rubber type; (3) Laboratory storage time; (4) Laboratory storage condition; (5) Laboratory batch replication; (6) Laboratory mixing time; (7) Field mixing time; (8) Laboratory test temperature; (9) Force-Ductility elongation rates; and (10) Asphalt grade. It was found that mixing temperature, mixing time, rubber type, and asphalt grade all have significant effects upon the behavior of asphalt-rubber mixtures. Significant variability was also noticed in different laboratory batch replications. Varying laboratory test temperature and force-ductility elongation rate revealed further differences in asphalt-rubber mixtures.